Membandingkan Empat Paradigma Rekayasa Perangkat Lunak - Rusli, Muhammad; Ziveria, Mira (I-STATEMENT, 2016)
This study aimed to compare the four paradigms of software engineering. Software became the machine that controls decision-making in the business world, serves as the basis of all forms of services and modern scientific research. The software is attached to any kind of system: transportation, medical, telecommunications, military, industrial processes, entertainment, office products and others. The method used to compare four software paradigm that Waterfall Model, Prototyping, Spiral Model, and Fourth-Generation. The software really can not escape from modern life. Therefore, it needs the technology to be used by people who build computer software and we also have to be able to develop it in a proper way. Technology includes a process, a series of methods and a series of tools called software engineering.